2017
DOI: 10.1007/s00415-017-8550-8
|View full text |Cite
|
Sign up to set email alerts
|

Higher blood–brain barrier permeability is associated with higher white matter hyperintensities burden

Abstract: The pathogenesis of white matter hyperintensities (WMH) is incompletely understood but blood-brain barrier (BBB) dysfunction may play a key role. This study aimed to investigate the relationship between BBB permeability and the severity of WMH burden. Consecutive participants without symptomatic stroke history presented for physical examination were recruited in this cross-sectional study and divided into three WMH burden groups according to total Fazekas scores. They received dynamic contrast-enhanced-magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 30 publications
5
43
0
1
Order By: Relevance
“…Subsequent reports focused on chronic edema due to a primary blood brain barrier dysfunction [ 8 ], which is supported by the evidence of increased albumin concentration within the interstitial space [ 14 ]. Indeed, more recent clinical data on dynamic MRI demonstrated increased gadolinium leakage into WMH, supporting in vivo the hypothesis of increased blood brain barrier permeability [ 15 ]. Interestingly, however, no disruption of endothelial tight junctions has been proven [ 14 ], yet endothelial cells were shown to express markers of activation [ 16 ].…”
Section: Wmh Pathology and Putative Pathophysiologymentioning
confidence: 69%
“…Subsequent reports focused on chronic edema due to a primary blood brain barrier dysfunction [ 8 ], which is supported by the evidence of increased albumin concentration within the interstitial space [ 14 ]. Indeed, more recent clinical data on dynamic MRI demonstrated increased gadolinium leakage into WMH, supporting in vivo the hypothesis of increased blood brain barrier permeability [ 15 ]. Interestingly, however, no disruption of endothelial tight junctions has been proven [ 14 ], yet endothelial cells were shown to express markers of activation [ 16 ].…”
Section: Wmh Pathology and Putative Pathophysiologymentioning
confidence: 69%
“…Dynamic contrast-enhanced (DCE)-MRI combined with an appropriate pharmacokinetics model is a reliable method to quantitatively evaluate BBB permeability ( 5 ). Using DCE-MRI method, previous cross-sectional studies reported compromised BBB integrity in patients with lacunar stroke, WMH, and mild vascular cognitive impairment (mVCI) ( 6 10 ). Moreover, a longitudinal study ( 11 ) revealed the association between poor functional outcome and increased BBB permeability in cSVD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, higher load of WMH is associated with adverse age-associated cognitive outcomes, such as slowed processing speed and increased risk of AD dementia 40,41 . In the absence of frank neurodegenerative phenotypes, age-associated WMH is frequently presumed secondary to cerebral vascular endotheliopathies resulting in increased BBB leakage and activation of CNS immune system, leading to reactive gliosis 40,[42][43][44][45] . In this model, endothelial cells play a central role.…”
Section: Discussionmentioning
confidence: 99%